Influence of Patient Setting and Dedicated Limb Salvage Efforts on Outcomes in Charcot-Related Foot Ulcer - Schmidt, Brian M. (Int J Low Extrem Wounds, 2019)
Charcot neuroarthropathy is a devastating consequence of diabetes mellitus and peripheral neuropathy. Because of its rarity, the condition is often misdiagnosed or poorly managed. When misadventure occurs, patients with Charcot neuroarthropathy can suffer ulceration, infection, amputation, and death. When patients have Charcot-related foot ulcers, the risks are amplified. Utilizing advanced electronic medical record analysis, a 30-month investigation was undertaken to determine if patients with diabetes mellitus and a concomitant diagnosis of Charcot-related foot ulcer were at greater risk of complications because of location setting of initial treatment for their condition. Charcot foot–related ulcers that are diagnosed in the outpatient setting had established foot specialist care. The outpatient management of the condition lead to a significant reduction in the amount of admissions to a higher acuity setting. However, patient outcomes did not vary once established and dedicated limb salvage efforts were employed. In this large contemporary population managed in a tertiary health system, patients with Charcot-related foot ulcer had negative outcomes when they were initially treated in an inpatient setting and had a significantly greater likelihood of readmission as compared with individuals who had established focused limb salvage care.